PENERAPAN DESIGN THINKING PADA PERANCANGAN UI/UX WEBSITE BOOTCHIN COFFE - Frayoga, Angga; Nilawati, Nilawati; Sany, Ezrifal (Jurnal Manajamen Informatika Jayakarta, 2024)
Developing a website with a good user interface (UI) and user experience (UX) is crucial in meeting customer needs and ensuring the success of online businesses. This research examines the application of the Design Thinking method in the UI/UX design process for the Bootchin Coffee website, an e-commerce platform that focuses on premium coffee products. This study employs a qualitative approach with key stages including understanding, observation, ideation, prototyping, and testing. Data is collected through interviews with potential users, competitor analysis, and observation. Additionally, this study explores user-centered design perspectives, encompassing aesthetics, functionality, and user satisfaction. The results of the research show that the application of Design Thinking in the UI/UX design of the Bootchin Coffee website enhances user interaction with the site. A more intuitive interface design, an improved understanding of user needs, and an overall enhanced user experience are the primary outcomes of this research. User acceptance testing also demonstrates a positive response from users to the implemented changes. Thus, this research provides recommendations for web developers and business owners to adopt the Design Thinking approach in designing their websites to meet the increasing demands of online consumers for a high-quality online experience. This study is expected to contribute to the development of UI/UX design and user experience knowledge and offer practical guidance to business owners seeking to improve the quality of their websites through the application of Design Thinking principles.